The genetic and epigenetic regulation of CD55 and its pathway analysis in colon cancer - Liu, Jiawei; Fu, Ning; Yang, Zhenbang; Li, Ang; Wu, Hongjiao; Jin, Ye; Song, Qinqin; Ji, Shanshan; Xu, Hongxue; Zhang, Zhi; Zhang, Xuemei (Frontiers in Immunology, 2023)
Background CD55 plays an important role in the development of colon cancer. This study aims to evaluate the expression of CD55 in colon cancer and discover how it is regulated by transcriptional factors and miRNA. Methods The expression of CD55 was explored by TIMER2.0, UALCAN, and Human Protein Atlas (HPA) databases. TRANSFAC and Contra v3 were used to predict the potential binding sites of transcription factors in the CD55 promoter. TargetScan and starBase v2.0 were used to predict the potential binding ability of miRNAs to the 3′ untranslated region (3′UTR) of CD55. SurvivalMeth was used to explore the differentially methylated sites in the CD55 promoter. Western blotting was used to detect the expression of TFCP2 and CD55. Dual-luciferase reporter assay and chromatin immunoprecipitation (ChIP) assay were performed to determine the targeting relationship of TFCP2, NF-κB, or miR-27a-3p with CD55. CD55-related genes were explored by constructing a protein–protein interaction (PPI) network and performing pathway analysis by Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG). Results CD55 was highly expressed in colon cancer tissues. The mRNA and protein expression levels of TFCP2 were reduced by si-TFCP2. NF-κB mRNA was obviously reduced by NF-κB inhibitor and increased by NF-κB activator. CD55 protein was also inhibited by miR-27a-3p. Dual-luciferase reporter assays showed that after knocking down TFCP2 or inhibiting NF-κB, the promoter activity of CD55 was decreased by 21% and 70%, respectively; after activating NF-κB, the promoter activity of CD55 increased by 2.3 times. As TFCP2 or NF-κB binding site was mutated, the transcriptional activity of CD55 was significantly decreased. ChIP assay showed that TFCP2 and NF-κB combined to the promoter of CD55. The luciferase activity of CD55 3′UTR decreased after being co-transfected with miR-27a-3p mimics and increased by miR-27a-3p antagomir. As the miR-27a-3p binding site was mutated, we did not find any significant effect of miR-27a-3p on reporter activity. PPI network assay revealed a set of CD55-related genes, which included CFP, CFB, C4A, and C4B. GO and KEGG analyses revealed that the target genes occur more frequently in immune-related pathways. Conclusion Our results indicated that CD55 is regulated by TFCP2, NF-κB, miR-27a-3p, and several immune-related genes, which in turn affects colon cancer.